KONTINUITAS TRADISI RATIB DAN PENGARUHNYA DI PALEMBANG ABAD XX–XXI - Muhammad Aknan; Jufri Suyuthi Pulungan; Munir Munir (Medina-te : Jurnal Studi Islam, 2020)
The phenomenon of the Ratib Tradition in Palembang still exists in the midst of today's modern era, of course the Ratib tradition that has long beenrooted in Palembang experiences continuity and discontinuity over the years and times that have passed. There fore this research wast oreveal the sustainability of this Ratib tradition and itspreservation process. This research was a field research with qualitative research type. Data collection was carried out through observation, interviews, documentation and historical studies to see and match the old traditions with the present. The results of this study indicated that the Rātib tradition in Palembang has continued till this day. This phenomenon was in accord ance with George Ritzer's theory of cultural continuity. Namely, Rātib practitioners who believed in the value of prestigewhenpracticing Rātib, and Rātib had a positive impactifit is practiced consistently. Further more, the preservation of the Rātib tradition in Palembang was done through local religious wisdom such as: marriage, circumcision, birth and moving house. In addition, there were agents that played a role in the preservation of Rātib in a structured and massive manner, such as: social organizations, social communities and also the exis tence of motives in every practice of the Rātib tradition in Palembang.